Menentukan Panjang Pipa Terpendek Untuk Pemasangan Jaringan Pipa PDAM Di Kecamatan Padang Timur Kota Padang - Rina, Iswan; Putri, Nurweni (UIN Imam Bonjol Padang, 2022)
This paper will show the completion of PDAM data by determining the shortest pipe length from PDAM data, in other words finding the shortest pipe length from the tree model that is formed.Â In this PDAM pipe network problem, the distance from each pipe is determined from one area to another. In this study, each PDAM pipe has a different distance between one pipe and another. So with this problem we need a way to determine the shortest pipe length from each PDAM pipe between regions. By determining the length of the shortest pipe so that the shortest distance can be obtained from the use of the pipe. After obtaining the shortest distance, this research will be able to obtain a model in the form of a graph, namely Tree and will look for the shortest pipe length between one area and another for the PDAM pipeline network in the city of Padang.Â In this case, Padang Timur was chosen as the object of research because of the ineffective use of the PDAM pipe network. The region using the Graph method is expected to be able to determine the shortest pipe length using a pipe network so that it will be more economical and practical to implement.